The Impact of Technology Integration on Student Learning Outcomes - Zhao Ma, Xianhua; Ertmer, Patricia Annian; Pelgrumen, Cees Petrus Mariana; Watsonta, John Robert; Sengha Tanu, Michaele Chin (Journal of Teaching and Learning, 2024)
The rapid advancement of information and communication technology (ICT) has significantly influenced various domains, including education. Recognized as a pivotal element in enhancing teaching quality and improving student learning outcomes, technology plays an essential role in modern education. This study examines the integration of technology in education and its impact on student learning outcomes in Shenzhen, China. Specifically, it focuses on how technology is utilized in classrooms and its effects on academic performance, critical thinking, problem-solving, and collaboration skills. Utilizing a qualitative research methodology with a case study design, the study gathers data through in-depth interviews, participatory observations, and document analysis involving students, educators, and school administrators. Thematic analysis is employed to extract key themes and insights from the participants' experiences. Findings reveal that technology integration positively influences student engagement and skill acquisition, despite persistent challenges such as insufficient teacher training and infrastructure limitations. The study concludes with actionable recommendations to optimize the use of technology in education, aiming to further enhance student learning outcomes.